A experiência estética na cidade e suas implicações éticas: transformação urbana e promoção do bem comum no espaço público de Belo Horizonte - Tadeu Starling Perdigao (2009)
This work focuses on the issue of aesthetic experience in the city, in order to investigate possible implications and developments of ethical nature in citizens everyday life, through the analysis of the relation between urban transformation process and the promotion of common good in the public space of Belo Horizonte. As specific object of study, among the innumerable elements that configure the physical dimension of the citys public spaces, it was chosen a set of permanence spaces and spaces that provide support to displacements of pedestrians in the area inside the current perimeter of Avenue do Contorno, which was defined as research universe. The approached spaces correspond tosquares of distinct characteristics, spaces remained of urban transformation, as well as linear spaces potentially rich in the capacity of receiving the citizens in their journeys through the city. Through direct observation procedures, aleatory displacements, establishment of journeys and photographic records accomplished in the area originally designed to Belo Horizonte by Engineer Aarão Reis in the XIX century, diverse data was raised which enables to make considerations about the need of assuring a good quality public space to the citizens. The hypothesis defended is that the city, when aesthetically experienced, can provide the subject of conditions for its improvement as citizen. Accordingly, the work proposes a reflection on the interlacing, in publicspace, of the concept of aesthetic experience and of ethical issues involved in this kind of experience and started by it.